The second intracellular loop of the yeast Trk1 potassium transporter is involved in regulation of activity, and interaction with 14-3-3 proteins - Masaryk, Jakub; Kale, Deepika; Pohl, Pavel; Ruiz-Castilla, Francisco J; Zimmermannová, Olga; Obšilová, Veronika; Ramos, José; Sychrová, Hana (Computational and structural biotechnology journal, 2023)
Potassium is an essential intracellular ion, and a sufficient intracellular concentration of it is crucial for many processes; therefore it is fundamental for cells to precisely regulate K+ uptake and efflux through the plasma membrane. The uniporter Trk1 is a key player in K+ acquisition in yeasts. The TRK1 gene is expressed at a low and stable level; thus the activity of the transporter needs to be regulated at a posttranslational level. S. cerevisiae Trk1 changes its activity and affinity for potassium ion quickly and according to both internal and external concentrations of K+, as well as the membrane potential. The molecular basis of these changes has not been elucidated, though phosphorylation is thought to play an important role. In this study, we examined the role of the second, short, and highly conserved intracellular hydrophilic loop of Trk1 (IL2), and identified two phosphorylable residues (Ser882 and Thr900) as very important for 1) the structure of the loop and consequently for the targeting of Trk1 to the plasma membrane, and 2) the upregulation of the transporter's activity reaching maximal affinity under low external K+ conditions. Moreover, we identified three residues (Thr155, Ser414, and Thr900) within the Trk1 protein as strong candidates for interaction with 14-3-3 regulatory proteins, and showed, in an in vitro experiment, that phosphorylated Thr900 of the IL2 indeed binds to both isoforms of yeast 14-3-3 proteins, Bmh1 and Bmh2.
Keywords: Saccharomyces cerevisiae; Trk1; Potassium ion uptake; Phosphorylation; 14–3–3 proteins